Biotechnology Foundations - O'Grady, Jack (Open textbook library., 2013)
Given the broad definition of biotechnology applications and products, it is easy to see how there is enormous overlap within the fields of cellular biology, microbiology, chemistry, and biomedical engineering. It is the goal of this textbook to provide foundational knowledge to begin building your biotechnology toolkit and enter an exciting career of making a difference through biotechnology. This textbook first explores the fundamentals of laboratory science and biotechnology. Unit 1 begins with a dive into the foundation of biology and chemistry by asking what is life and what are the molecules of life? The end of the unit offers a primer into laboratory science; preparing solutions and operating basic lab equipment. Unit 2 brings readers through a vital tool of biomanufacturing, understanding the growth and control of microbes. Many biotechnology products are made by harnessing the work of microbes, and this unit explores this invisible and intriguing world of microorganisms. The final unit, molecular biotechnology, offers a more in-depth look at how biological molecules such as DNA and protein are manipulated into creating useful products.